Perioperative nursing based on fast-track surgery for patients undergoing neuroendoscope-assisted microvascular decompression for trigeminal neuralgia (快速康复外科在完全神经内镜下三叉神经微血管减压术围手术期护理中的应用) - CHEN Liyun (陈黎芸); CAI Fengting (蔡凤婷) (Journal of International Translational Medicine Limited, 2021)
Objective To explore the effect of perioperative nursing interventions based on fast-track surgery (FTS) for patients undergoing neuroendoscope-assisted microvascular decompression (EMVD) for trigeminal neuralgia. Methods Totally 100 patients undergoing EMVD for trigeminal neuralgia were enrolled and randomly divided into control group and observation group, with 50 cases in each group. The control group received routine care during the operative period, and the observation group received nursing interventions based on FTS theory. The anxiety status was evaluated by Self-rating Anxiety Scale (SAS), and incidence of postoperative complications such as nausea and vomiting was compared between two groups. Results The score of SAS in the observation group was lower than that in the control group before and after surgery (P＜0. 05). The incidences of nausea and vomiting, urinary tract infection in the observation group was lower than those in the control group (P＜0. 05). Conclusion Nursing interventions based on FTS concept can effectively relieve the anxiety status of patients undergoing EMVD for trigeminal neuralgia, and reduce the risk of postoperative complications such as nausea and vomiting. (目的 探讨快速康复外科(FTS)理念在完全神经内镜下微血管减压术患者围术期护理中的应用效果。方法 100例接受完全神经内镜下三叉神经微血管减压术治疗的患者随机分成对照组和观察组, 各50例。围手术期间, 对照组接受常规护理, 观察组接受基于FTS理念的护理干预。评估2组患者焦虑状况, 统计恶心、呕吐等并发症发生情况。结果 观察组术前和术后SAS评分均低于对照组, 差异有统计学意义(P＜0. 05)。观察组恶心呕吐、尿路感染发生率低于对照组, 差异有统计学意义(P＜0. 05)。结论 基于FTS理念的护理干预可有效缓解完全神经内镜下微血管减压术患者的焦虑情绪, 减少术后并发症发生风险。)